SOCIO-LEGAL THOUGHT OF THE JADID MOVEMENT AND ITS CONTINUITY IN THE EDUCATIONAL REFORMS OF MODERN UZBEKISTAN - Mukhitdinova Firyuza Abdurashidovna; Mukhiddinova Dilyora Sherzodovna (Bright Mind Publishing, 2025)
The article examines the social-legal thinking of the Jadid movement with a special focus on the role of education and upbringing in building a just society based on the rule of law. The Jadids viewed education as a legal and civic institution that was central to the formation of responsible citizens. By establishing modern schools, creating new textbooks, and promoting civic values, they strove to create an enlightened and law-abiding community. The study also includes a comparative approach with Turkey and Germany and shows how the Jazidis adapted international educational experiences to the local realities of Central Asia. In addition, it analyzes how modern Uzbekistan under President Shavkat Mirziyoyev continues this mission through comprehensive reforms in education, innovation and youth development.
Keywords: Jadidism, legal culture, civic education, President Shavkat Mirziyoyev, reforms in Uzbekistan, youth, modernization, comparative legal studies, Turkey, Germany.